ANALISIS KURIKULUM REGGIO EMILIA - Tri Sayekti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
The curriculum is a written plan based on the principles of child development program in accordance with the standards of achievement, which contains the ultimate goal of development and learning of children, the experience gained when children reach the goal. The role of teachers and parents in achieving the objectives, materials needed for the implementation of the curriculum. Approach Reggio Emilia to early childhood education is committed to the manufacturing environment for learning that will enhance and facilitate the establishment of the power of thinking of children through the establishment of all expression, communication, and cognitive language or “through the synthesis of all the expressive, communicative, and cognitive languages”. Reggio Emilia approach to early childhood education has attracted perhatianpendidik, researchers and almost anyone who is interested in early childhood education with the best practices. The National Association for the Education of Young Children (NAEYC) has revised its practice of developmentally appropriate (DAP). The guidelines also included examples of the Reggio Emilia approach. Currently, the Reggio Emilia approach has been adopted in the United States, Britain, New Zealand, Australia, India and many other countries. Indonesia has a great curriculum, only more leads to the teacher as the source of everything. There would need to make changes in the program for early childhood learning better future.